Impact of Treatment Interruption on the Effectiveness of Interleukin (IL)-17A Inhibitors in Plaque Psoriasis: A Retrospective Analysis - Jiang J; Zhang M; Li M (International Journal of General Medicine)
Jin Jiang,1 Meihua Zhang,2 Mi Li1 1Department of Dermatology, Liyang People’s Hospital, Liyang, People’s Republic of China; 2Department of Dermatology, Jiangsu Provincial People’s Hospital, Nanjing, People’s Republic of ChinaCorrespondence: Mi Li, Department of Dermatology, Liyang People’s Hospital, 70 Jianshe West Road, Liyang, Changzhou, Jiangsu, 213300, People’s Republic of China, Email limicherry159009@163.comBackground: Plaque psoriasis is a chronic, recurrent, immune-mediated inflammatory skin disease. This study aimed to investigate effectiveness of interleukin (IL)-17A inhibitor treatment and effectiveness after treatment interruption in plaque psoriasis patients and analyze the related factors.Methods: This study retrospectively collected clinical characteristics and related treatment status of plaque psoriasis patients treated with IL-17A inhibitors, and evaluated the treatment effectiveness, reasons for treatment interruption, effectiveness after treatment interruption, and risk factors affecting treatment effectiveness.Results: This study ultimately included 106 patients with plaque psoriasis, including 61 males (57.55%) and 45 females (42.45%), aged 41.0 (31.0– 54.0) years and with a disease duration of 12.0 (8.0– 20.0) months. Among them, 71 cases (67%) achieved PASI90 after receiving IL-17A inhibitor treatment, and 35 cases (33.02%) achieved PASI75. A total of 50 patients (50/106, 47.17%) interrupted treatment, 23 patients (23/50, 46%) maintained a therapeutic effect of PASI90 or above, and 27 patients (27/50, 54%) had a therapeutic effect lower than PASI75, with median time of treatment interruption of 1.0 (1.0– 3.5) months. Univariate analysis findings showed that duration of IL-17A inhibitor treatment interruption and reasons for interruption had significant statistical significance on treatment effectiveness (all P< 0.05). In multivariate analysis, treatment interruption (OR=7.154, 95% CI: 2.528– 20.24) and reasons such as stress/anxiety (OR: 14.889, 95% CI: 1.160– 23.480) were risk factors affecting treatment effectiveness.Conclusion: Interleukin (IL)-17A inhibitor treatment interruption plays critical effects on the treatment of plaque psoriasis. Early and long-term adherence to IL-17A inhibitor treatment can control the course of the disease and improve the long-term health of psoriasis patients.Keywords: plaque psoriasis, interleukin (IL)-17A inhibitors, interrupt, COVID-19 pandemic, treatment outcomes